System reliability-based Direct Design Method for space frames with cold–formed steel hollow sections. (1st July 2018) - Liu, Wenyu; Zhang, Hao; Rasmussen, Kim
Highlights: Advanced nonlinear finite element analysis can design a steel frame as a system. A reliability framework of developing system resistance factors for the Direct Design Method is presented. Sixteen 3D cold-formed steel frames with hollow locally stable cross-sections were analysed for their system reliabilities. The relationships between system resistance factors and system reliability index were established. Abstract: Design-by-analysis methods for steel structures are receiving considerable attention from professional engineers, researchers and standard-writing groups. Designing by analysis, termed as the Direct Design Method (DDM), is premised on the use of geometric nonlinear inelastic finite element analysis to determine the ultimate strength of steel structural frames and subsequently incorporating a system resistance factor ( ϕs ) to account for the effects of uncertainties in geometric parameters, stiffness and strength. This paper outlines the DDM in the context of cold-formed compact Hollow Steel Sections (HSS), including the reliability analysis framework at system level underpinning the Method. The system resistance factors for a series of representative 3D frames with hollow locally stable cross-sections are derived.